Kupu sebagai Sumber Inspirasi Penciptaan Dhapur Keris - Vinsha Arissadewa; Kuntadi Wasi Darmojo (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2023)
The unique life cycle of a butterfly is known as a perfect metamorphosis, seen through the aesthetic aspect of the transformation of shape into a butterfly, so that this insect is often used as a symbol of perfection by some people. The concept of metamorphosis is quite relevant to keris culture, considering that the development of contemporary keris culture leads to art objects that put forward the value of meaning and symbols. The purpose of the creation of this work is to realize the shape of the dhapur keris by visualizing the aesthetics of the life cycle of the butterfly (caterpillar and butterfly) as a symbol and hope. The creation of this final project uses a three-stage method, namely: the exploration stage, the design stage, and the embodiment stage. As for the analysis of the work produced with an aesthetic approach from the concept of thought of Haryono Haryoguritno, namely the external criteria consisting of: aspects of garap, iron, pamor, steel (waja), and wangun. The resulting works are two kris works, namely the dhapur wyalangga keris and the dhapur butterfly keris which refer to the shape of the Javanese kris, and each work contains a philosophical meaning about the cycle of life.